Vagyok aki vagyok, portré Krassó Miklósról - Jávor, István (Hungary, 2007)
Miklós Krassó was one of the great thinkers of the 20th century. Following the failure of the '56 revolution in Hungary he fled to London where he lived until a tragic accident ended his life in 1986. All his life he had been a man of words whose suggestive personality fascinated many, yet he refused to put down his thoughts on paper except for one study he had written about Trotsky. All he has left behind are two video recordings. This film is an edited version of these.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films